用你认为最简便的方法计算:(1)(﹣8)+(﹣11)﹣13﹣(﹣12); (2)﹣36×( ﹣ ﹣ )÷(﹣2);(3)
1个回答
(1)原式=﹣8﹣11﹣(13﹣12)=﹣8﹣11﹣1=﹣20;
(2)原式=(9﹣4﹣3)÷2=2÷2=1;
(3)原式=﹣4 ×
×
=﹣
;
(4)原式=
﹣4+4=
﹣(4﹣4)=
。
相关问题
117÷13+36×12怎么用简便方法计算
用简便方法计算.4.05÷[1.8×(3.36-2.86)] =
【(8/7+6/1)÷8/5-4/3】×11/6简便方法计算(3/2+5/1)÷15/7×11/6简便方法计算
用简便方法计算(步骤)7/8×12/13+7/8÷13=?
用简便方法计算[5/8]×[1/13]+[3/8]÷13 575×99
用简便方法计算11/12×13/16+13/12×1/16
13/17÷8+3/17×1/8用简便方法计算
用简便方法计算!7/3-(6/13÷9/26+3/8) 4/25÷[(2/5+1/3)×9/11] (1/2+2/3-5
用简便方法计算.[5/12]×[1/13]-[1/4]÷13
简便计算(1)24-[11/13−213](2)12×(56−59)×27(3)[3/13×45+1013÷54−0.8